1984
DOI: 10.1007/bf00200050
|View full text |Cite
|
Sign up to set email alerts
|

Carrier and adjuvant properties of liposome-borne tumor-specific antigens

Abstract: The purpose of this study was to examine (1) the association of tumor extract proteins with phospholipid vesicles of varying physiochemical properties, and (2) the adjuvant and carrier properties of liposome-borne tumor antigens in the in vivo induction of an antitumor immune response. Cell surface antigens of the 3-methylcholanthrene-induced fibrosarcoma of C3H/HeJ mice, MCA-F, were extracted using 2.5% 1-butanol. Crude and electrofocused antigen preparations capable of eliciting a protective antitumor immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Antigens that are presented on cell membranes or on membrane-like structures (e. g. liposomes) are usually more immunogenic than antigens in "soluble form". For instance, LeGrue [19] reported that a partially purified butanol extract adsorbed to liposomes displayed a specific activity 20-to 50-fold greater than the soluble antigen. Moreover, the immunogenicity of liposome-associated antigens is affected by the characteristics of the liposomes (e. g. charge, fluidity, mode of antigen incorporation) and also by the presence of adjuvants, co-incorporated with the antigen in the same liposome preparation [ 12].…”
Section: Introductionmentioning
confidence: 98%
“…Antigens that are presented on cell membranes or on membrane-like structures (e. g. liposomes) are usually more immunogenic than antigens in "soluble form". For instance, LeGrue [19] reported that a partially purified butanol extract adsorbed to liposomes displayed a specific activity 20-to 50-fold greater than the soluble antigen. Moreover, the immunogenicity of liposome-associated antigens is affected by the characteristics of the liposomes (e. g. charge, fluidity, mode of antigen incorporation) and also by the presence of adjuvants, co-incorporated with the antigen in the same liposome preparation [ 12].…”
Section: Introductionmentioning
confidence: 98%
“…Second, the protein-to-PL ratio may affect the immunogenicity of liposome-presented antigens, as described for the humoral response against protein antigens [10,38]. Liposomal incorporation of crude or semi-purified TAA extracts can augment specific immune reactions against TAA [16,25,30,33,34]. In these studies a variety of tumour models, extraction techniques, and liposome types has been employed.…”
Section: Discussionmentioning
confidence: 99%
“…Because liposomes are biodegradable, have little toxicity, are not immunogenic, and may target specific certain cells in vivo, they are advantageous as immunological adjuvants. 12 For improving the immunogenic potential of a specific antigen, such as glycolipids, proteins, and antigens to dangerous viruses, among others, liposomes are effective adjuvants. During in vivo tests antibody-sensitized liposomes, which have frequently shown highly positive outcomes in in-vitro investigations that frequently take place without macrophages, immunoglobulins, or components of the complement system, failed.…”
Section: Immune Liposomementioning
confidence: 99%